Gender and bubbles in experimental markets with positive and negative expectation feedback - Lu, Zhou (2022)
We investigate the effect of gender on the price deviation (bubble) from the fundamental value in a learning-to-forecast experiment. Our results show that gender plays a more prominent role in markets with positive expectation feedback than in markets with negative feedback. In both types of markets, market prices tend to depart more from the fundamental values when there are more male participants in the market.